Rheology, Crystallinity, and Mechanical Investigation of Interlayer Adhesion Strength by Thermal Annealing of Polyetherimide (PEI/ULTEM 1010) Parts Produced by 3D Printing - Yilmaz, Musa; Yilmaz, Necip Fazil; Kalkan, Mahmut Furkan (SPRINGER)
Fused deposition modeling (FDM) is a 3D printing technology in which the melt extrusion method is used for the production of thermoplastic parts. 3D printed thermoplastic materials produced by this method suffer from a particularly significant problem, however, namely poor interfacial bond formation that results in weak mechanical performance. This work proposes a thermal process to enhance the strength of the interlayer adhesion of 3D printed PEI thermoplastic materials. The annealing process was determined as a suitable post-processing procedure and was the focus of this work. Annealing was carried out in an oven at temperatures of 220, 225, 230, and 235 degrees C; it was determined that annealing performed at 225 degrees C in particular was highly desirable in terms of enhancing interlayer adhesion strength. In this work, characterization (FTIR, XRD, and SEM) and mechanical (tensile, bending, and hardness) analyses of 3D printed PEI were performed to better understand the strength of interlayer adhesion and overcome a mechanical performance limitation of this material. According to the tensile, bending, and hardness test results, the greatest improvements were found as increase of 10, 5, and 12%, respectively.
Keywords: rheology; PEI; interlayer tensile strength; crystallinity; annealing; 3D printing